CHEMICAL COMPOSITION OF THE FRUITS OF THE PLANT ZIZIPHUS JUJUBA AND THEIR APPLICATION IN FOLK MEDICINE (Scientific journal of the Fergana State University, 2023)
The plant Ziziphus jujuba was popularly called “chilonjiida” or “unabi” and has long been used in folk medicine. It is nutritious, high-calorie and healing. The article describes the history of the origin of unabi, its healing properties, composition, application in folk and traditional medicine, as well as the results of the research